2009
DOI: 10.1038/nchembio.250
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting proteins for degradation

Abstract: Protein degradation plays a central role in many cellular functions. Misfolded and damaged proteins are removed from the cell to avoid toxicity. The concentrations of regulatory proteins are adjusted by degradation at the appropriate time. Both foreign and native proteins are digested into small peptides as part of the adaptive immune response. In eukaryotic cells, an ATP-dependent protease called the proteasome is responsible for much of this proteolysis. Proteins are targeted for proteasomal degradation by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
231
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(243 citation statements)
references
References 128 publications
5
231
0
Order By: Relevance
“…31 Our findings do not exclude the possibility that NOXA turnover may occur by a trans inititation mechanism in vivo. 16 Consistent with this two-part degron model, 16 NOXA may associate with an uncharacterized polyubiquitinated adaptor protein that facilitates its targeting to the 19S RP and subsequently, degradation of NOXA is initiated from the unstructured region of NOXA. Further studies are necessary to distinguish this possibility from an alternative model that NOXA binds directly with sufficiently high affinity to the 19S RP, followed by degradation commencing from its unstructured region.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…31 Our findings do not exclude the possibility that NOXA turnover may occur by a trans inititation mechanism in vivo. 16 Consistent with this two-part degron model, 16 NOXA may associate with an uncharacterized polyubiquitinated adaptor protein that facilitates its targeting to the 19S RP and subsequently, degradation of NOXA is initiated from the unstructured region of NOXA. Further studies are necessary to distinguish this possibility from an alternative model that NOXA binds directly with sufficiently high affinity to the 19S RP, followed by degradation commencing from its unstructured region.…”
Section: Discussionmentioning
confidence: 78%
“…Various proteins, which can be degraded by an Ub-independent pathway, possess unstructured regions that may act as initiation sites for their subsequent degradation. 12,16 Multiple predictive tools suggested that the N-terminal region of NOXA has a high probability to be disordered (Supplementary Figure S4). Moreover, the thermal denaturation curve for synthetic NOXA (s-NOXA) showed no evidence of cooperative unfolding, which suggested that the protein was intrinsically unfolded, whereas DN-MCL-1-WT showed co-operative unfolding (Supplementary Figure S5A).…”
mentioning
confidence: 99%
“…148 The rest of cohesin complex is apparently spared, owing to the subunit selectivity of the Arg/N-end rule pathway. 122,[234][235][236] The identity of a residue at the N-terminus of a C-terminal fragment of Scc1/Rad21 varies in a tellingly constrained manner. Specifically, this residue is Arg in the budding yeast S. cerevisiae, Asn in the fission yeast Schizosaccharomyces pombe, Cys in D. melanogaster, and Glu in mammals.…”
Section: A Fragment Of Cohesinmentioning
confidence: 99%
“…For ubiquitin-dependent degrons, the recognition/binding phase is accomplished by covalently attached polyubiquitin moieties that recognize one or more subunits of the proteasomal complex (46,47). For ubiquitin-independent degradation, mechanisms that directly involve the target substrate's polypeptide chain are utilized (12,18,44).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanism of Degron Function-The currently accepted "two-component" model of proteasomal degradation posits two phases in degron function (45,46): (i) proteasome recognition and binding and (ii) initiation of insertion into the proteolytic chamber. For ubiquitin-dependent degrons, the recognition/binding phase is accomplished by covalently attached polyubiquitin moieties that recognize one or more subunits of the proteasomal complex (46,47).…”
Section: Discussionmentioning
confidence: 99%